Suplementasi CO2 Membuka Potensi Biomassa, Lipid, dan Karotenoid pada Mikroalga Coelastrella sp. strain Saripa - Akhmad Ikhsan, Maulana; Nyoman Semad, Antara; I Wayan , Arnata; Ni Wayan Sri, Agustini; Susanti, Hani (Innovation Centre for Tropical Sciences, 2025)
Microalgae are a group of photosynthetic microorganisms widely distributed in various habitats, especially in aquatic environment. This study aimed to evaluate the effects of carbon dioxide (CO2) gas supplementation on the growth and biomass production of the microalgae Coelastrella sp. strain Saripa, as well as the lipid and carotenoid contents produced. Additionally, color changes during the growth process were observed as physiological indicators of the microalgae's response to CO2 treatments and pH changes during growth. The experiment was conducted using a Completely Randomized Design. CO2 was supplemented at 0, 25, and 50 ml volumes. The results showed that different CO2 supplementations influenced the pH change, ranging from 6 to 8.4 during cultivation. The 50 ml CO2 supplementation at pH 6 resulted in the highest biomass production (0.418±0.022 mg/l), lipid production (46%), and total carotenoids (21%). Under this condition, the culture color changed gradually, correlated with the change of chlorophylls and carotenoid contents. Statistical analysis (α = 0.05) confirmed that CO2 supplementations significantly affected biomass, lipid, and carotenoid productions. In conclusion, Coelastrella sp. strain Saripa demonstrated potentials in reducing atmospheric CO2, providing the biomass as lipid and carotenoid bioresources. Keywords: Coelastrella sp., microalgae, CO2 gas supplementation